A Bibliographic Assessment Using the Degrees of Publication Method: Medicinal Plants from the Rural Greater Mpigi Region (Uganda). (15th January 2021) - Schultz, Fabien; Anywar, Godwin; Quave, Cassandra Leah; Garbe, Leif-Alexander
Abstract : In ethnopharmacological research, many field assessment tools exist. Yet, these miss that critical point of how to really determine which species merit the costly lab studies, e.g., evaluation of traditional use via pharmacological assays and isolation of bioactive secondary metabolites. This gap can be filled with the introduction of a new tool for literature assessment: the Degrees of Publication (DoPs). In this study, its application is illustrated through an extensive bibliographic assessment of 16 medicinal plant species that were recently identified in the Greater Mpigi region of Uganda as being frequently used by local traditional healers in the treatment of medical disorders (namely, Albizia coriaria, Cassine buchananii, Combretum molle, Erythrina abyssinica, Ficus saussureana, Harungana madagascariensis, Leucas calostachys, Microgramma lycopodioides, Morella kandtiana, Plectranthus hadiensis, Securidaca longipedunculata, Sesamum calycinum subsp. angustifolium, Solanum aculeastrum, Toddalia asiatica, Warburgia ugandensis, and Zanthoxylum chalybeum ). These species are suspected to be understudied, and a thorough bibliographic assessment has not been previously performed. Thus, the objectives of our study were to undertake a comparative assessment of the degree to which each of these plant species has been studied in the past, including evaluation of the quality of the journals where results were published in. The determination of the DoPs enabled successful assessment of the degrees to which each individual plant species has been studied so far, while also taking into account the methodological "research chain of ethnopharmacology" from ethnobotanical studies ("traditional use") to pharmacological assays ("bioactivity") and finally to pharmacognostic research ("structure elucidation"). The significance of a research paper was assessed by determining whether its journal and publishing house were members of the Committee on Publication Ethics ( COPE). In total, 634 peer-reviewed publications were reviewed covering the period of 1960–2019, 53.3% of which were published in journals and by publishing houses affiliated with COPE (338 publications). The literature assessment resulted in the identification of understudied plants among the selected species. The majority of plants reviewed have not been sufficiently studied; six species were classified as being highly understudied and three more as being understudied: C. buchananii, F. saussureana, L. calostachys, M. lycopodioides, M. kandtiana, and S. calycinum subsp. angustifolium and A. coriaria, P. hadiensis, and S. aculeastrum, respectively. The newly introduced DoPs are a useful tool for the selection of traditionally used species for future laboratory studies, especially for pharmacological bioassays, isolation procedures, and drug discovery strategies.